Malaysian Tualang Honey and its potential anti-cancer properties: a review - Ahmad Firdaus Khalid; Tan, Jun Jie; Yong, Yoke Keong (Penerbit Universiti Kebangsaan Malaysia, 2018)
The use of honey as a therapeutic agent dates back at 8000 years and has markedly increased interest into its potential health benefits. The by-products of the flower nectar have a complex chemical composition which promotes benefits in underlying mechanism of human diseases. Malaysian Tualang Honey (MTH) is a multifloral jungle honey produced by the rock bee (Apis dorsata). This review consolidates the results of carious studies involving biochemical assays of tissue culture and animal trials of anti-cancer properties of MTH. Often studied in the context of breast cancer cell lines, MTH has promising data for possible mechanisms in anti-cancer activity. These include apoptosis via depolarization of the mitochondrial membrane, caspase-dependent apoptosis, reduction of angiogenesis and the promotion of cell cycle arrest without posing cytotoxic effect on normal cell lines. Despite positive outcomes in tissue cultures, the oral administration of MTH in breast cancer animal models showed slower tumour progression, reduction in tumour size and better grading of histological features. The alleviation of breast carcinogenesis via modulation of hematologic, estrogenic and apoptotic activities promotes MTH as a promising anticancer agent. With confidence in a conclusion that MTH is a useful treatment for cancer, further experimental and clinical studies should be conducted.